Daimond itihas mahiticosh - Joshi S.H.; Kulkarani M.R.; Shelake Raghunath, Kulkarni Shilpa & Dandekar Sunita (Daymond publications, Pune, 2009)
History
UGC XIth Five Year Plan 2009-2010
MARATHI
Keywords: Daimond itihas mahiticosh; History; History